Navy Ship Deployments : New Approaches -- Background and Issues for Congress. (U.S. Congressional Research., 2007)
Reviews developments in Navy deployments and potential resulting issues for Congress. Discusses new kinds of naval formations, more flexible forward-deployment schedules, forward-homeporting additional Navy ships, long-duration deployments with crew rotation, and global fleet stations.